OPTIMIZATION OF PIPE DIAMETER AND TOPOGRAPHICAL COMPRESSOR GAS TRANSPORTATION SYSTEM FOR THE INCREASED DEMAND FOR GAS - TAMPATI FAHDINAR (NIM : 22208306); Pembimbing : Dr. Ir. Arsegianto, M.sc., RICKO
The development of gas transportation systems costly; two main components are the costs of pipeline and compressor costs. There are several important issues in designing the pipeline, including the power of pipes and pipe flow capacity. The problems discussed in this thesis is how to build an optimum gas transportation system to transport gas scenario with increasing, but still meet the specified requirements. In this thesis, a study conducted on the pipe which has a length of 100 km, with a large increase of gas transport for 20 years, where the lapse of the first year of 400 MMSCFD of gas transport, and then increased by 200 MMSCFD every 5 year. Model using hypothetical data in accordance with general conditions in the field. This study used the help of the simulator program. The prices as a parameter in the economic calculations are determined based on the trends and estimates that close to the appropriate price range in the industry today. The diameter of the pipe tested in this thesis, namely, 28-inch diameter pipe, 30 inch, 32 inch, 34 inch, and 36 inches. The method used is heuristic method. Based on the results of simulation and calculation, it can be concluded that the design of the optimum gas transportation system for this case study is a network of pipes with a diameter of pipe 34 inches, with the use of power by 1097 HP compressor, installed in the year to 15. Selection of pipeline design is based on minimum total cost incurred, amounting to US$ 226.157.762.